Understanding Gen Z Workers in Career Management at Banks: A Literature Review - Kurniawan Setyantoro; Faizal Rizqi; Surya Raharja; Puji Harto (LifeSciFi, 2025)
This study aims to uncover the career aspirations of Gen Z workers at PT Bank Rakyat Indonesia (BRI), considering their characteristics that are different from the previous generation. Gen Z is predicted to occupy managerial positions in the next 5-10 years and if handled well, their presence often pushes companies to modernize communication, leadership styles, and DEI (diversity, equity, inclusion) practices. This study examines previous literature that focuses on Gen Z workers in frontliner, marketing, and officer positions at Bank BRI. The literature is then reviewed to see the overall picture and draw conclusions about this topic. The results of the study are expected to provide an understanding of Gen Z's career expectations and become the basis for human resource management strategies at Bank BRI for the sustainability of the organization. This study fills the gap in previous research that focuses more on students and has not touched on the cultural context and work experience of Gen Z directly in organizations in Indonesia.